Productivity of castor bean plants intercropped at different plant densities with Urochloa ruziziensis - Carlos F. dos S. Cordeiro; Fábio R. Echer; Lucas H. T. Pires; José E. Creste (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Castor bean is an important raw material to produce biofuel in Brazil and can be grown in several regions of the country due to its good adaptation and tolerance to high temperatures and water deficit. The objective of this study was to evaluate the productivity of castor bean plants intercropped at different plant densities with Urochloa ruziziensis. The experiment was conducted in a randomized block design with four replications, using a 4 × 2 factorial arrangement, consisting of four plant densities (13,574, 24,512, 36,816, and 40,723 plants ha-1) of castor bean and two crop systems (single crop, and intercrop with Urochloa ruziziensis). The data were subjected to analyses of variance and regression, and means were compared by the Tukey’s test (p < 0.05). The intercrop system reduced the number of pods per plant by 15%, but it did not significantly affect the castor bean grain yield. Increasing plant density reduced linearly the proportion of plants harvested, reaching 22.1%, from the lowest to the highest plant density used; the highest grain yield was achieved using 36,816 plants ha-1 for both intercrop and single crop systems. Intercropping castor bean with U. ruziziensis does not reduce the castor bean grain yield and is an alternative to produce biomass for following crops, especially in production environments with low fertility soils, high temperatures, and infrequent rainfall.